Encryption of agonistic motifs for TLR4 into artificial antigens augmented the maturation of antigen-presenting cells - Ito, Masaki; Hayashi, Kazumi; Minamisawa, Tamiko; Homma, Sadamu; Koido, Shigeo; Shiba, Kiyotaka (PLOS ONE, 2017)
Adjuvants are indispensable for achieving a sufficient immune response from vaccinations. From a functional viewpoint, adjuvants are classified into two categories: “physical adjuvants” increase the efficacy of antigen presentation by antigen-presenting cells (APC) and “signal adjuvants” induce the maturation of APC. Our previous study has demonstrated that a physical adjuvant can be encrypted into proteinous antigens by creating artificial proteins from combinatorial assemblages of epitope peptides and those peptide sequences having propensities to form certain protein structures (motif programming). However, the artificial antigens still require a signal adjuvant to maturate the APC; for example, co-administration of the Toll-like receptor 4 (TLR4) agonist monophosphoryl lipid A (MPLA) was required to induce an in vivo immunoreaction. In this study, we further modified the previous artificial antigens by appending the peptide motifs, which have been reported to have agonistic activity for TLR4, to create “adjuvant-free” antigens. The created antigens with triple TLR4 agonistic motifs in their C-terminus have activated NF-κB signaling pathways through TLR4. These proteins also induced the production of the inflammatory cytokine TNF-α, and the expression of the co-stimulatory molecule CD40 in APC, supporting the maturation of APC in vitro. Unexpectedly, these signal adjuvant-encrypted proteins have lost their ability to be physical adjuvants because they did not induce cytotoxic T lymphocytes (CTL) in vivo, while the parental proteins induced CTL. These results confirmed that the manifestation of a motif’s function is context-dependent and simple addition does not always work for motif-programing. Further optimization of the molecular context of the TLR4 agonistic motifs in antigens should be required to create adjuvant-free antigens.